Character Values of ‘Cening” for EFL Learners on English Drama Show: Sekala and Niskala - Putu Arsana, Anak Agung; Putri Cahayadewi, Ni Putu; Erika Kencana Dewi, Ni Putu (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2025)
This paper explores the implementation of character education for EFL learners through the medium of an English drama performance. Centered on the character Cening, the study investigates how theatrical shows can serve as a vehicle for instilling core values such as courage, integrity, and solidarity. The research examines the vital role of character building within language instruction, specifically its impact on personal growth, communicative proficiency, and analytical reasoning. By utilizing drama-based strategies like storytelling and role-playing, the paper demonstrates how students can more deeply comprehend narrative themes and ethical lessons. Ultimately, the author argues that integrating drama into the curriculum effectively shapes the identities of EFL learners, preparing them to become successful and principled individuals.